2003
DOI: 10.3354/ame033041
|View full text |Cite
|
Sign up to set email alerts
|

Activity and diversity of bacterial cells with high and low nucleic acid content

Abstract: In most aquatic environments, at least 2 subpopulations of bacterial cells can be discriminated by flow cytometry based on their nucleic acid content. Recent investigations have shown that the cells with a high nucleic acid (HNA) content have a higher cell-specific activity (CSA) cell than those with a low nucleic acid (LNA) content. In this study, the CSA and biomass-specific activities (BSA) of HNA and LNA cells from different aquatic ecosystems, including marine, brackish and freshwater, were investigated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
125
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(143 citation statements)
references
References 26 publications
(35 reference statements)
15
125
1
1
Order By: Relevance
“…However, contrasting results have been reported, with some studies in coastal sites showing that the HNA and LNA populations are different, whereas others found similar taxonomic composition (Servais et al, 2003;Longnecker et al, 2005). Moreover, it is possible that the HNA cells growing (and then being grazed) in our experiment belonged to a limited number of taxa responding to the phytoplankton bloom by rapid growth, thus overriding the effect of the heavy HNF bacterivory; this is a life strategy suggested for freshwater bacteria of the genus Limnohabitans (Šimek et al, 2014).…”
Section: Discussionmentioning
confidence: 67%
“…However, contrasting results have been reported, with some studies in coastal sites showing that the HNA and LNA populations are different, whereas others found similar taxonomic composition (Servais et al, 2003;Longnecker et al, 2005). Moreover, it is possible that the HNA cells growing (and then being grazed) in our experiment belonged to a limited number of taxa responding to the phytoplankton bloom by rapid growth, thus overriding the effect of the heavy HNF bacterivory; this is a life strategy suggested for freshwater bacteria of the genus Limnohabitans (Šimek et al, 2014).…”
Section: Discussionmentioning
confidence: 67%
“…It was reported that coastal seas had a lower proportion of LNA bacteria, such as on a transect from Delaware to the Sargasso Sea (35%), or the Grand Banks (22-42%) (Li et al 1995;Li and Dickie 2001). In contrast, there was a higher proportion of LNA bacteria found in the coastal Canet lagoon (57%; Servais et al 2003), eastern Mediterranean Sea (65%), North Atlantic (64%; Li et al 1995) and the Gulf of Mexico (62%; Jochem et al 2004). In comparison, only a few reports are available on LNA and HNA bacteria in freshwater environments (Ni et al 2015;Read et al 2015).…”
Section: Introductionmentioning
confidence: 69%
“…The HNA bacteria were considered the most active members of a given community while LNA were regarded as inactive, dead or dormant cells (17,26,27). HNA and LNA were also considered to be members of the same phylotypes (11,38). However some have demonstrated that LNA are different phylotypes from HNA cells (12,31,45) and that indeed LNA can be responsible for a significant portion of total heterotrophic metabolism (1,22,31,34,45), all observations from oligotrophic systems as open oceans.…”
Section: Introductionmentioning
confidence: 99%